Al-Maqrīzī's al-Ḫabar ʻan al-bašar - Maqrīzī, Aḥmad ibn ʻAlī, 1364-1442. (Bibliotheca Maqriziana, 2017)
Al-Maqrīzī's (d. 845/1442) last work, al-Ḫabar ʿan al-bašar , was completed a year before his death. This volume, edited by Jaakko Hämeen-Anttila, covers the history of pre-Islamic Iran from the Creation to the Parthians. Al-Maqrīzī's work shows how Arab historians integrated Iran into world history and how they harmonized various currents of historiography (Middle Persian historiography, Islamic sacred history, Greek and Latin historiography). Among al-Ḫabar' s sources is Kitāb Hurūšiyūš , the Arabic translation of Paulus Orosius' Historiarum adversum paganos libri vii. This source has only been preserved in one defective copy, and al-Maqrīzī's text helps to fill in some of its lacunae.